A study of fluid intake from beverages in a sample of healthy French children, adolescents and adults - Bellisle, F (Nature Publishing Group, 2010)
BACKGROUND/OBJECTIVES: To assess the intake of fluid in healthy French children, adolescents, adults and seniors, considering amounts, types of beverages, time and place of consumption. SUBJECTS/METHODS: Data regarding fluid intake were extracted and analyzed from the National Intake Survey, which was conducted in quota samples of the French population (Comportement et Consommations Alimentaires en France study). Seven-day questionnaires were administered to free-living individuals in 2002–2003. A total of 566 children (aged 6–11 years), 333 adolescents (aged 12–19 years), 831 adults (aged 20–54 years) and 443 seniors (aged ⩾55 years) were included in this study. RESULTS: The average total intake of fluid was 1–1.3 l per day depending on age groups. Water accounted for about one-half of daily fluid intake. The contribution of other types of beverages varied with age (for example, dairy drinks in children and adolescents; alcoholic drinks in adults and seniors). Intake of sodas (including regular and light) was highest in adolescents (169 ml a day). Beverages were mainly consumed at home during meals. CONCLUSIONS: This is the first description of fluid intake in French children, adolescents, adults and seniors, considering amounts, types of beverages, time and place of intake. It shows that water is the main source of fluid in all age groups. Selection of various types of beverages is different according to age.